Attitudes about police and race in the United States 2020-2021: Mean-level trends and associations with political attitudes, psychiatric problems, and COVID-19 outcomes. - Catherine Vitro; D Angus Clark; Carter Sherman; Mary M Heitzeg; Brian M Hicks (PLoS ONE, 2022)
The murder of George Floyd and subsequent mass protest movement in the summer of 2020 brought policing, race, and police brutality to the forefront of American political discourse. We examined mean-levels of attitudes about police and race using online surveys administered at five time points from June 2020 to October 2021 (n ~ 1000 at each wave) to adults living in the United States. There was a small increase in pro-police attitudes over this time (d = .24), and some evidence that mean-levels of pro-police attitudes increased more for Black participants (d = .51) than White participants (d = .20), and more for Democrats (d = .40) than Republicans (d = .15). Pro-police attitudes were much lower among Black participants than White participants (mean d = -1.04), and-relative to political independents-lower among Democrats (mean d = -.66) and higher among Republicans (mean d = .72). Pro-police attitudes had large associations with a variety of conservative or right-wing political attitudes (e.g., approval of Donald Trump) and COVID-19 variables (e.g., disapproval of government mandates and restrictions), but were unrelated to psychiatric problems and substance use. These results validate a new measure of police attitudes, provide information on trends in police attitudes over the 15 months following the largest mass protests against police brutality in American history, and begin to establish the nomological network of police attitudes, finding that pro-police attitudes are firmly within the right-wing coalition of American politics.